Modified CMIS factors predicting Chinese women’s mental health information seeking in Douyin - Zhang, Xin; Kamarudin, Syafila; Tang, Qingqing (Redfame Publishing Inc., 2024)
The popularity of Douyin (known as TikTok overseas) could provide additional mental health information services to Chinese women. However, the factors that influence women to seek mental health information services in Douyin are still understudied. The study applied the Comprehensive Model of Information Seeking (CMIS) to Chinese women’s mental health information seeking behaviors on Douyin to examine this. The study used a questionnaire (N=505), and the data analysis was conducted using partial least squares structural equation modeling (PLS-SEM). SmartPLS 4.0 was the primary data analysis technology. Results showed that direct experience, beliefs, salience, and characteristics of mental health information could significantly affect the utility of mental health information on Douyin. In addition, utility, social support, and characteristics directly affect Chinese women’s mental health information seeking. Moreover, utility partially mediates the relationship between direct experience, beliefs, salience, characteristics, and mental health information seeking. Rather than targeting specific diseases or pan-health information, this study demonstrates the possibility of applying CMIS to mental health information seeking. This insight could contribute to Douyin and government health interventions to better meet the mental health information needs of Chinese women.